Comparative Study of Islamic Financial Values at Wahdah Islamiyah Gorontalo City and Baznas Gorontalo City in Serving the Muslim Community in Gorontalo City - Saifuddin Podungge; Sri dewi yusuf (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to compare the application of Islamic financial values in two non-profit institutions serving Muslims in Gorontalo City, namely the Regional Leadership Council (DPD) Wahdah Islamiyah, which is one of the Islamic organizations in Indonesia domiciled in Gorontalo City, and the National Amil Zakat Agency (BAZNAS) Gorontalo City, which is a non-structural government agency. This research uses a descriptive qualitative approach with a literature review technique of research findings that discuss the two institutions. The research found that although both institutions are based on Islamic law in their financial management, the focus of implementation has different characteristics. Wahdah Islamiyah emphasizes the principles of deliberation, trust, justice, and dependence on Allah in the budget decision-making process, while BAZNAS Gorontalo City emphasizes accountability, effectiveness of zakat distribution, and transformation of zakat recipients into zakat givers through the ZMART program. This journal recommends value collaboration between the two institutions to create a more sustainable Islamic financial management system.